Oral contraceptive pills: A risk factor for retinal vascular occlusion in in-vitro fertilization patients - Rohina S Aggarwal; Vineet V Mishra; Somesh V Aggarwal (Wolters Kluwer Medknow Publications, 2013)
Retinal vascular occlusion is the most common cause of retinopathy leading to severe visual loss in all age groups. Central retinal vein occlusion (CRVO) is usually seen in older age group and is often associated with systemic vascular diseases. Although the exact cause and effect relationship has not been proven, central retinal vein occlusion has been associated with various systemic pathological conditions, hence a direct review of systems toward the various systemic and local factors predisposing the central retinal vein occlusion is advocated. We describe the development of central retinal venous occlusion with associated cystoid macular edema (CME) in two healthy infertile women who were recruited for in vitro fertilization cycle for infertility. Predisposing risk factors associated with central retinal vein occlusion are obesity, sedentary life style, smoking, and some systemic diseases such as hyperlipidemia, hypertension, associated autoimmune disorders e.g., antiphospholipid antibody syndrome, lupus, diabetes mellitus, cardiovascular disorders, bleeding or clotting disorders, vasculitis, closed-head trauma, alcohol consumption, primary open-angle glaucoma or angle-closure glaucoma.In our patients, they were ruled out afterdoing allpertaining investigations. The cases were managed with further avoidance of oral contraceptives and intra-vitreal injections of Bevacizumab (Avastin), an anti-vascular endothelial growth factor (anti-VEGF drug) and Triamcinolone acetonide (a long acting synthetic steroid). Hence, even if no systemic diseases are detected. Physical examinations are recommended periodically for young women on oral contraceptive pills.